(untitled) (Development Service Industry Management, 2025)
The article is devoted to the study of robotics as one of the key innovative tools for the development of the international hotel and tourism industry. The study reveals the meaning of the concept of «robotics», examines its modern directions and features of its application in world-class hotels. The relevance of the topic is emphasized in the context of increased global competition, instability in the labor market, changes in consumer behavior and the active introduction of digital technologies into the hospitality industry. Special attention is paid to the analysis of various types of robotic solutions that are implemented in the activities of hotel enterprises, such as service and logistics workers, information assistants, automated management systems. Their functions, advantages, as well as their impact on improving the level of customer service, optimizing staff work and reducing operating costs are highlighted. Based on the study, practical recommendations are proposed for the integration of robotic systems into the operational activities of the international hotel and tourism industry. The recommendations are aimed at improving the quality of service, forming a sustainable image, strengthening competitive positions and adapting to the challenges of digital transformation. Finally, the importance of a comprehensive and strategic approach to the implementation of robotics in the hotel and tourism sector is emphasized. Promising areas of further research are outlined, including the adaptation of robotic solutions to the cultural characteristics of regions, compliance with ethical standards and the development of new models of "guest - robot" interaction. The following scientific methods are used in the article - analysis of specialized literature, systematization and comparison of successful cases of international hotel brands, the method of analogies, as well as the method of forecasting, which allowed for an in-depth study of modern trends in the field of robotics in the hospitality industry.